A cryptic complex of species related to Transversotrema licinum Manter, 1970 from fishes of the Indo-West Pacific, including descriptions of ten new species of Transversotrema Witenberg, 1944 (Digenea: Transversotrematidae) - Hunter, Janet A.; Cribb, Thomas H. (Zootaxa, 2012)
Transversotrema licinum Manter, 1970 was described from two species of fishes from Moreton Bay, Queensland, and sub-sequently reported from 13 further species from six families in the Indo–West Pacific region. This study records specimensmorphologically similar to T. licinum from 48 fish species from 11 families. A combined analysis of the second internaltranscribed spacer region (ITS2) of ribosomal DNA and morphological data revealed a complex of at least 15 species andfrom these data ten new species of Transversotrema Witenberg, 1944 are described here. T. licinum sensu stricto is char-acterised in terms of morphology, distinct genotype, wide host distribution (Kyphosidae, Lutjanidae, Monodactylidae,Mugilidae, Pomacentridae and Sparidae) and, at present, is known only in Moreton Bay. The following new species areproposed: T. atkinsoni n. sp. from nemipterids from Heron Island (southern GBR) and Ningaloo Reef (Western Australia);T. borboleta n. sp. from chaetodontids and lutjanines (Lutjanidae) from Lizard Island and Heron Island; T. cardinalis n.sp. from lutjanines and a haemulid from Lizard Island; T. carmenae n. sp. from nemipterids from Lizard Island; T. dam-sella n. sp. from pomacentrids, a labrid and a mugilid from Lizard Island; T. espanola n. sp. from lutjanines from Heronand Lizard Islands; T. fusilieri n. sp. from caesionines (Lutjanidae) from Lizard Island; T. manteri n. sp. from caesioninesfrom Lizard Island and Ningaloo Reef; T. nova n. sp. from a nemipterid from New Caledonia; and T. witenbergi n. sp.from caesionines from Heron Island. Transversotrema borboleta n. sp. is itself probably a complex of at least three closelyrelated species but these are not yet sufficiently well delineated to allow separate descriptions. Four putative species re-ferred to as Species A–D recognised from molecular analysis have not been described because of insufficient data. Mostspecies are evidently strongly restricted to families or subfamilies of fishes. Only T. licinum appears to be genuinely eu-ryxenic. Transversotrema borboleta infects chaetodontids and lutjanids but the nature of the distribution may be an indi-cation that it represents a species complex. Most of the species appear to have restricted ranges, being absent from susceptible host species at some localities.